Pengaruh Supervisi Kepala Sekolah dan Motivasi Kerja terhadap Kinerja Guru di Madrasah Aliyah Darussalam Ngesong Jombang - Irfan Arifin Nurrohman; Suwandi Suwandi (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The aims of the research were 1) Analyzing the influence of principal supervision on teacher performance at Islamic Senior High School Darussalam Ngesong Jombang. 2) Analyze the influence of work motivation on teacher performance at Islamic Senior High School Darussalam Ngesong Jombang. 3) Analyze the simultaneous influence of principal supervision and work motivation on teacher performance at Islamic Senior High School Darussalam Ngesong Jombang. The method and approach used is a quantitative method. With the application in the form of lifts which are analyzed statistically using SPSS. The following research produced several findings, the first of which indicated that there was no correlation or influence between the supervision of school principals and the performance of teaching staff or teachers at Islamic Senior High School Darussalam Ngesong Jombang. This can be seen from the coefficient value of 0.209 > 0.05 and the calculated t value of 1.298 > t table 1,713. The second indicates that there is a correlation between work motivation and the performance of teaching staff or teachers at Islamic Senior High School Darussalam Ngesong with the calculated t coefficient value being greater than the t table, the calculated t value 1.991 > t table 1.713. And finally, there is simultaneously an influence or correlation between the principal's supervision and work motivation on the performance of teaching staff or teachers at MA Darussala Ngesong with a constanta significance value of 0.000 < 0.05 and a calculated F value of 8.095 > F table 3.422